Resisted sprint training for the acceleration phase of sprinting - Cronin, J.; Hansen, K. T. (Strength and Conditioning Journal, 2006)
First, the biomechanical differences between the acceleration phase and he maximum velocity phase of sprinting are considered. Second, research on the various resisted sprinting techniques is examined, linking these techniques to the biomechanics of the acceleration phase. Some suggestions are made regarding the application of these findings to the training of athletes.